2013
DOI: 10.3109/14767058.2013.858319
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and paraoxonase activity in cord blood from obese mothers

Abstract: Essential obesity in pregnancy is associated with hyperleptinemia. PON1 exerts an antioxidant role; therefore, our results demonstrated that obesity exposes to an increased susceptibility to oxidative damage in both mothers and newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
4
17
1
Order By: Relevance
“…Leptin, a proinflammatory adipokine, not only is elevated in the maternal circulation of pregnant obese women but also is higher in the cord blood of their children than in children whose mothers are not obese. 32 Conversely, adiponectin, which has antiinflammatory properties and has shown inverse associations with asthma symptoms 33 and airway inflammation, 34 is decreased in obesity and is also decreased in newborns of obese mothers. 35 Alternatively, maternal obesity may influence the pathogenesis of asthma through exposure of the developing fetus to different dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, a proinflammatory adipokine, not only is elevated in the maternal circulation of pregnant obese women but also is higher in the cord blood of their children than in children whose mothers are not obese. 32 Conversely, adiponectin, which has antiinflammatory properties and has shown inverse associations with asthma symptoms 33 and airway inflammation, 34 is decreased in obesity and is also decreased in newborns of obese mothers. 35 Alternatively, maternal obesity may influence the pathogenesis of asthma through exposure of the developing fetus to different dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that obesity and metabolic syndrome are characterized by chronic inflammation (Hotamisligil 2006). Pregnancy is a stage having increased susceptibility to oxidative stress (Casanueva and Viteri 2003; Patil et al 2007) and effects may be enhanced in obese mothers (Ferretti et al 2013; Rajasingam et al 2009; Sen et al 2014). Furthermore, studies have demonstrated that obese pregnant women may have enhanced systemic and placental inflammation (Stewart et al 2007) and increased pro-inflammatory cytokine expression in the placenta (Challier et al 2008), suggesting that maternal obesity and traffic air pollution exposure may act synergistically to impact fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pregnancy is a state having enhanced susceptibility to oxidative stress (Casanueva and Viteri 2003; Patil et al 2007) which has implications for fetal growth (Weber et al 2014). These associations may be further modified by maternal obesity (Ferretti et al 2013; Rajasingam et al 2009; Sen et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord leptin levels are elevated in obese pregnancies (Ferretti et al, 2014;Karakosta et al, 2013;Walsh et al, 2014) and neonatal circulating leptin is elevated in offspring of obese mice (Samuelsson et al, 2008). Therefore, early life hyperleptinaemia may drive sympathetic hyperstimulation in the developing renal-cardiovascular system, leading to hypertension and cardiovascular dysfunction in adulthood (Briffa et al, 2014).…”
Section: Cardiovascular Systemmentioning
confidence: 99%